Intentional content in psychopathologies requires an expanded interpretivism. (2019) - Slors, Marc; Francken, Jolien C.; Strijbos, Derek
Abstract: We argue that the explanatory role of intentional content in connecting symptoms in a network approach to psychopathology hinges neither on causality nor on rationality. Instead, we argue that it hinges on a pluralistic body of practical and clinical know-how. Incorporating this practical approach to intentional state ascription in psychopathological cases expands and improves traditional interpretivism.